Plant‐associated Bacillus spp. alter life‐history traits of the specialist insect Brevicoryne brassicae L. (27th August 2015) - Gadhave, Kiran R.; Gange, Alan C.
Abstract: Numerous soil‐dwelling Bacillus species form mutualistic relationships with plants, in which the hosts derive an array of benefits, including the alteration of nutrient and chemical content. Despite such ubiquitous and intimate Bacillus –plant associations, the role of these bacteria in affecting the performance of specialist foliage‐feeding insects is largely unknown. We studied the effects of individual and mixed treatments of Bacillus cereus, Bacillus subtilis and Bacillus amyloliquefaciens on calabrese growth and important life‐history characteristics and the population dynamics of the specialist phloem‐feeding aphid Brevicoryne brassicae . All Bacillus species negatively affected the life‐history traits and supressed the populations of B. brassicae in varying magnitudes. The differences in aphid populations and number of leaves infested increased swiftly towards the end of the experiment and peaked 71 days after sowing. Bacillus cereus was the most effective treatment in reducing B. brassicae growth rates, followed by the mixture of species, B. amyloliquefaciens and B. subtilis treatments. However, no synergistic or additive effects of bacteria were found. Overall, plant growth promoting Bacillus species significantly suppress the growth and development of B. brassicae and show great potential for use in an integrated biological control programme for this pest.